Immunogenicity of Recombinant DNA Vaccine Encoding Non-Structural Protein-1 Dengue Virus Serotype-2 in Balb/c Mice - Elitha Pulungan (Microbiology Indonesia, 2021)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus (DENV) which spread widely in tropical and subtropical regions of the world. DENV is a single-positive strand RNA virus with a genome size of Â± 11kb which encodes three structural proteins, seven non-structural proteins, and two untranslated regions (UTR). The non-structural protein-1 (NS1) of DENV is known to have important role in dengue pathogenesis also promising to be developed as dengue vaccine. Lately, novel vaccine approach by DNA immunization have given new perspective for a safe, stable, and immunogenic vaccine platform. Previously, we have successfully construct DNA vaccine encoding NS1 protein of DENV2 (pUNS1) which express recombinant NS1 protein in-vitro. Thus, in this current study the ability of pUNS1 to induce humoral immune response will be further analyzed by in mice immunization. Methods: Sixteen BALB/c mice aged of 4 weeks were immunized 3 times with 100 Âµg of pUNS1 or pUMVC4a on 2 week time interval. Blood sampling was carried out just before immunization and termination was done 2 week after last immunization. Titer from individual mice sera against DENV-2 were measure with in-house ELISA. Results: IgG against NS1 protein of DENV2 titer from mice group immunized with recombinant pUNS1 shown high ELISA absorbancies, 5 times higher than pUMVC4a group. This result suggest the ability of pUNS1 to induce humoral immune response against NS1 DENV-2 in-vivo. Conclusion: Recombinant pUNS1 can induce humoral immune response in mice.